On the origin of the architect: Architects and xenía in the ancient Greek theatre - Weir, Simon (Interstices: Journal of Architecture and Related Arts, 2016)
Ubiquitous in ancient Greek culture, the ethical principle of xenía may broadly translate as hospitality to strangers, doing so through taking interpersonal, political, and architectural form. Since xenía includes the accommodation of foreign guests, some evidence of xenía in architecture is logically found in houses and hostels, but surprisingly more evidence surrounds Athens’ Theatre of Dionysus, on stage in Aristophanes’ Peace and Euripides’ Cyclops, and off stage through the architects elected to look after the sanctuary of the theatre. This paper reveals the principle of xenía permeating the professional work of the architect to such a degree that Vitruvius and Demosthenes would reproach even slight digressions from the principle, and Vitruvius would call the education of xenía the most valuable thing to outlast a shipwreck.